83.5k views
1 vote
Please help me! Can't figure these out.

Please help me! Can't figure these out.-example-1
User Raphnguyen
by
5.0k points

2 Answers

0 votes
For this case we have the following expression:

√(x+3) + 4 = 5
To solve it, we follow the following steps:
We subtract 4 on both sides of the equation:

√(x+3) + 4 - 4 = 5 - 4
We rewrite the expression:

√(x+3) = 1
We square both sides of the equation:

(√(x+3))^2 = 1^2

x+3 = 1
We subtract 3 on both sides of the equation:

x + 3- 3 = 1 - 3
We rewrite the expression:

x= - 2
Answer:
The solution of the equation is:

x= - 2
User Kyle Humfeld
by
4.3k points
4 votes
√(x + 3) + 4 = 5

first subtract 4 from both sides to isolate the x.

√(x + 3) + 4 (-4) = 5 (-4)


√(x + 3) = 5 - 4


√(x + 3) = 1

Next, get rid of the root by squaring both sides


(√(x + 3))² = (1)²

x + 3 = 1

Finally, isolate the x. Subtract 3 from both sides

x + 3 (-3) = 1 (-3)

x = 1 - 3

x = -2

x = -2 is your answer

hope this helps
User Thanos Diacakis
by
5.0k points